Critical success factors of microcredit entrepreneurs - Johari, Nor Farizah (2014)
Poverty is being recognized and emphasized as important factors that lead to the downfall of other vital aspects such as national unity that could affect the stability of politics in Malaysia. Tragically, the poorest group in Malaysia is the original people of the land especially Malays.Viewing that Malays and Bumiputeras need to be assisted to exit from the clutch of poverty, many entrepreneurial programs are crafted by the government to correct this imbalance socio-economics.In order to support this endeavor, NGOs also get involve and one of them is the replicator of prominent microcredit program originated from Bangladesh; Amanah Ikhtiar Malaysia (AIM) who give tiny loan to its beneficiaries.After more than 2 decades operating, the record stated that AIM is the most successful microcredit provider in Malaysia. Therefore, this study seeks to determine the key success factors of AIM beneficiaries in becoming successful micro-entrepreneurs. The personally administered questionnaire was distributed to beneficiaries of Amanah Ikhtiar Malaysia (AIM).The questionnaire is derived from the similar study done among micro-entrepreneurs in West Africa and additional related literature from previous scholars. This study indicated that the AIM beneficiaries in Pahang have recorded increment in their income after joining AIM and they are no longer remaining in poverty status. It shows that the beneficiaries of AIM microcredit program have achieved the successful record as proven by previous impact studies and the factors could be exemplified by other microcredit programs beneficiaries. This study perhaps can add the breadth of knowledge of the microcredit programs specifically on the success factor of the micro-entrepreneurs in Malaysia.